EDITORIAL - Vongurai, Rawin (Scholar: Human Sciences, 2024)
The Scholar: Human Sciences, a journal encompassing the fields of humanities and social sciences, has earned acclaim in the Thailand Citation Index (TCI) as a prominent publication since 2015. It currently holds the esteemed TCI: TIER2 classification. We take great pride in presenting the latest issue, which features a collection of manuscripts that have undergone rigorous evaluation. Each submission has been meticulously reviewed through a blinded review process by three specialized reviewers from different institutions, both internal and external to the authors. This peer-reviewed accreditation ensures the scholarly quality and integrity of the published articles. This issue covers twenty-six articles. The first article titled “Measuring Satisfaction and Continuance Intention of Undergraduates towards E-Learning in Chengdu, China” evaluates the factors significantly influencing e-learning satisfaction and continuance intention among undergraduate dance choreography students at three private universities in Chengdu, China. The second article titled “Antecedents of Adult Students’ Behavioral Intention and Usage Behavior of Massive Open Online Courses in Chongqing, China” aims to investigate the factors influencing the behavioral intention and usage behavior of Massive Open Online Courses (MOOCs) among adult students in higher education. The third article titled “Understanding Significant Factors of Attitude and Purchase Intention of Online Customers Toward E-Commerce in China” studies the factors that shape the attitudes and purchase intentions of Chinese online shoppers in relation to online shopping within China. The fourth article titled “Predicting Significant Factors of Postgraduate Students to Use English Learning Apps in Kunming, China” delves into the determinants that shape the behavioral intention and use behavior of English learning apps among postgraduate students in Kunming, China. The fifth articled titled “Investigating Factors Affecting of Customers’ Satisfaction and Loyalty Towards Express Logistics and Its Internet Plus in Sichuan, China” provides effective thinking inspiration and strong decision support for express logistics enterprises to improve the service level of express logistics in the operation and management process and further helps them enhance their overall competitiveness and achieve sustainable development. The sixth article titled “Examining on Behavioral Intention and Use Behavior of Students Online Learning Systems: A Case of Vocational Collages in Jiangxi, China” proposes a causal relationship among perceived usefulness, perceived ease of use, attitude, perceived behavioral control, social influence, behavioral intentions, and use behavior. The seventh article titled “Examining Significant Factors of Satisfaction and Performance with Online Learning Among Graduate Students in Chengdu, China” investigates the factors that impact students’ satisfaction with and effectiveness of online learning within the context of four universities closely affiliated with the Ministry of Education in Chengdu. The eighth article titled “A Study on Intention and Behavior Towards English Learning Among Second-Year Students in Higher Vocational Colleges in Chengdu, China” investigates the interplay among various variables that influence individual behavior and intentions within the context of prior studies. The ninth article titled “Key Determinants for Users’ Intention to Use Smart Home Technology: A Case of Residents in Mianyang, Yibin and Wanzhou, China” investigate the various determinants that affect residents’ inclination to adopt smart home technology in the cities of Mianyang, Yibin, and Wanzhou, located in China. The tenth article titled “Evaluating Significant Factors of Graduate Students’ Satisfaction with Small Private Online Course in Chongqing, China” is to investigate the determinants that impact student satisfaction when utilizing Small Private Online Courses (SPOCs) in Chongqing, China. The eleventh article titled “Factors Influencing Behavioral Intention and Use Behavior of Junior Students to Use Ubiquitous Learning in Chengdu, China” aims to investigate the factors that influence the behavioral intention and behavior of third year college students when using ubiquitous Learning in Chengdu, Sichuan Province. The twelfth article titled “Tourism Mobile Applets: Factors Affecting Tourists’ Behavioral Intention and Use Behavior in Shanghai, China” delves into the factors influencing the behavioral intention and use behavior of Shanghai tourists towards Tourism Mobile Applets. The thirteenth article titled “Key Factors of Younger Generation Consumer’s Attitude and Intention to Use Online Shopping Live Broadcasting Platform in Chengdu China” studies the significant influencing factors of younger generation consumers’ attitudes and intentions toward online shopping live broadcasting platforms in Chengdu, China. The fourteenth article titled “An Empirical Study on Factors Affecting Satisfaction and Loyalty with Independent Institutions Among Vocational Students in Sichuan, China” examines the factors that affect students’ satisfaction and loyalty towards independent institutions in Chengdu, Sichuan province. The fifteenth article titled “Examining Parents on The Enhancement of Primary Students’ Behavioral Intention to Use Computer Painting in Chongqing, China” incorporates several critical variables, encompassing emotional value, economic value, social value, perceived usefulness, enjoyment, satisfaction, and behavioral intention. The sixteenth article titled “Determinants of Satisfaction and Loyalty with Thai Spa Products of Chinese in Deyang City of China with Travel Experience to Thailand” aims to determine the determinants of satisfaction and loyalty with Thai spa products of Chinese in Deyang city of China with travel experience to Thailand. The seventeenth article titled “A Research on the Influencing Factors of Fourth Year College Students’ Entrepreneurship Intention and Behavior in Chengdu, China” explores the determinants impacting the entrepreneurial aspirations and actions of university students located in Chengdu, China. The eighteenth article titled “An Examination of Factors Impacting Attitude, and Intention to Use Mobile Learning Among Female College Students in Guizhou, China” is to examine the determinants affecting the attitudes and intentions of female college students in Guizhou, China, regarding the adoption of mobile learning. The nineteenth article titled “Factors Impacting Customers’ Satisfaction, Loyalty, and Continuance Intention in Using Car Sharing Service Platform in Chengdu, China” aims to examine factors impacting customers’ satisfaction, loyalty, and continuance intention to use car-sharing services platforms. The twentieth article titled “Examining Students’ Behavioral Intention and Actual Usage of Mixed Painting Education: A Case of an Art School in Chengdu, China” delves into the determinants influencing students’ behavioral intention and actual usage of mixed painting education in the city of Chengdu, China. The twenty-first article titled “Understanding the Drive of Chinese Players’ Continuous Intention and Loyalty Towards Online Games in Wuhan, China” examines the factors impacting Chinese players’ continuous intention and loyalty towards online games in Wuhan, China. The twenty-second article titled “An Analysis of the Factors Impacting Satisfaction and Continued Intention to Use Digital Library: A Case Study of Universities in Chongqing, China” explores the influencing factors of students’ satisfaction and to continued intention to use digital libraries in Chongqing. The twenty-third article titled “Factors Influencing Consumers’ Co-Creation Value and Purchase Intention of the Virtual Brand Community in Guangdong, China” aims to investigate the key influencing factors of co-creation value and purchase intention of internet users in virtual brand communities in Guangdong Province, China. The twenty-fourth article titled “An Investigation on Factors Impacting Satisfaction and Continuance Intention to Use E-Learning Among University Lecturers in Zhejiang, China” aims to investigate factors contribute to the satisfaction and continuance intentions to use e-learning among university lecturers in Zhejiang, China. The twenty-fifth article titled “Factors Impacting Postgraduate Students’ Satisfaction and Continuance Intention with Online Education in Chengdu, China” examines the satisfaction and continuance intention of post-graduates pursuing a degree in accounting, translation, Chinese language and literature, and ideological and political education in Chengdu, China, for online learning. The twenty-sixth article titled “Examination of Influencing Factors of Postgraduate Students’ E-learning Satisfaction, and Continuance Intention in Chengdu, China” aims to investigate the factors that influence e-learning satisfaction, and continuance intention among postgraduate students in Chengdu, China.